Relasi Gereja, Negara, dan Masyarakat: Etika Kristen pada Ketaatan dan Tanggung Jawab: The Relationship Between Church, State, and Society: Christian Ethics on Obedience and Responsibility - Oey Natanael Winanto; Johnnie Manopo; Iswahyudi Iswahyudi (Journal of Religious and Socio-Cultural, 2023)
Christian ethics in the nation, state and society, the political attitude of the Christian faith adheres to the principle of theocracy, namely the call of Christians to declare and realize God's will in the life of the nation, state, and society. The purpose of this writing is to find out how the role of the church is in politics and to apply the Christian faith in the development of politics, nation, and state. The writing method used is a literature review with a Christian ethics study approach. The result of the discussion is that one of the responsibilities and roles of Christians in the life of the nation and state is related to their political awareness in the form of forming organizations or parties that take part in politics. Christian ethics is ethics that stems from the acknowledgment that Jesus Christ is God. It means that He is God who controls, regulates all movements, steps, and goals of Christian life, according to the tasks given to His people. Etika Kristen dalam berbangsa, bernegaradan bermasyarakat, maka sikap politik iman Kristen berpegang pada asas teokrasi, yaitu panggilan umat Kristen untuk menyatakan dan mewujudkan kehendak Tuhan dalam kehidupan berbangsa, bernegara dan bermasyarakat. Tujuan penulisan ini adalah menemukan bagaimana peran gereja dalam politik dan mengaplikasikan iman Kristen dalam pembangunan politik, berbangsa, dan bernegara. Metode penulisan yang digunakan adalah kajian literatur dengan pendekatan studi etika Kristen. Hasil pembahasan adalah salah satu tanggungjawab dan peranan umat Kristen dalam kehidupan berbangsa dan bernegara adalah menyangkut kesadaran politiknya dalam wujud pembentukan organisasi atau partai yang berkiprah di dalam politik. Etika Kristen adalah etika yang berpangkal pada pengakuan, bahwa Yesus Kristus adalah Tuhan. Artinya, bahwa Ia adalah Tuhan yang menguasai, mengatur seluruh gerak, langkah dan tujuan hidup umat Kristen, sesuai dengan tugas yang diberikan kepada umat-Nya.